2012
DOI: 10.1103/physrevc.86.064313
|View full text |Cite
|
Sign up to set email alerts
|

Pairing gaps in the Hartree-Fock-Bogoliubov theory with the Gogny D1S interaction

Abstract: As part of a program to study odd-A nuclei in the Hartree-Fock-Bogoliubov (HFB) theory, we have developed a new calculational tool to find the HFB minima of odd-A nuclei based on the gradient method and using interactions of Gogny's form. The HFB minimization includes both time-even and time-odd fields in the energy functional, avoiding the commonly used "filling approximation". Here we apply the method to calculate neutron pairing gaps in some representative isotope chains of spherical and deformed nuclei, na… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 34 publications
2
68
0
Order By: Relevance
“…The 32 Ar measurement, taken together with previously existing Coulomb excitation data for 32 Si [1998Ib01], yields the isoscalar and isovector multipole matrix elements for the transition between T =2 states in the A=32 system. Complementary Coulex and RDM measurements of 44,46 Ar were conducted at GANIL, France and Legnaro, Italy facilities [2009Zi01, 2010Me07], respectively. These experiments addressed the development of deformation and shape coexistence in the vicinity of the doubly magic 48 Ca, related to the weakening of the N =28 shell closure.…”
Section: 444648 Armentioning
confidence: 99%
“…The 32 Ar measurement, taken together with previously existing Coulomb excitation data for 32 Si [1998Ib01], yields the isoscalar and isovector multipole matrix elements for the transition between T =2 states in the A=32 system. Complementary Coulex and RDM measurements of 44,46 Ar were conducted at GANIL, France and Legnaro, Italy facilities [2009Zi01, 2010Me07], respectively. These experiments addressed the development of deformation and shape coexistence in the vicinity of the doubly magic 48 Ca, related to the weakening of the N =28 shell closure.…”
Section: 444648 Armentioning
confidence: 99%
“…We have developed new code to find the Hartree-Fock-Bogoliubov minima of the Gogny functional in axially symmetric nuclei, treating for the first time time-odd fields including the spin-dependent ones [8]. Applying the code to spin splittings in deformed nuclei, we found that the predicted splittings violated the GM rule more often than not.…”
mentioning
confidence: 99%
“…The description of the properties of odd nuclides has received considerable interest during recent years in the framework of mean-field theory [1,[6][7][8][9][10][11][12], where the OES of binding energies is the main constraint for the pairing interaction. As such, efforts have been devoted to understanding the different contributions to the OES and designing precise estimators for the pairing gap.…”
Section: Introductionmentioning
confidence: 99%